A controlled trial of nandrolone decanoate in the treatment of rheumatoid arthritis in postmenopausal women. Issue 3 (March 1987) - Bird, H A; Burkinshaw, L; Pearson, D; Atkinson, P J; Leatham, P A; Hill, J; Raven, A; Wright, V
Abstract : To determine whether an anabolic steroid had any benefit in the treatment of rheumatoid arthritis 47 patients entered a parallel group study. Twenty four received nandrolone decanoate 50 mg intramuscularly every third week for two years and 23 patients received no anabolic steroids. Other therapy was unaltered. Patients attended for clinical and biochemical assessments as well as the objective assessments of elementary body composition by in vivo neutron activation analysis and measurement of the mineral content of the distal femur by single photon absorptiometry on five occasions. A modest clinical deterioration (except for grip strength) was seen in both groups. No significant changes in calcium or alkaline phosphatase were seen. There was no significant change in total body calcium, total body phosphorus, body weight, or bone index/bone width measurements in either group. Significant increases occurred in total body nitrogen, total body potassium, haemoglobin, and packed cell volume (by six months) in the group treated with nandrolone decanoate. Comparison of 10 patients in the group treated with nandrolone decanoate also receiving oral steroid therapy with 14 patients in this group not receiving oral steroid therapy showed no significant differences. The main side effect of nandrolone decanoate was hoarseness. No radiological changes were seen. Nandrolone decanoate, in a dose that produces a significant anabolic effect, has no demonstrable action on bone metabolism in rheumatoid arthritis but may improve the chronic anaemia by six months.